An Anthropometric Study Of Stature Estimation From Little Finger Length In The Haryanvi Population (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Identifying a person is one of the most important aspects of a medicolegal inquiry.  Research has been done to assess stature using various body components. The  current study set out to determine whether little finger lengths are a reliable  indicator of stature and to compute regression models using the data that were  collected. The current study attempted to check the usefulness and calculate the  regression models in the estimation of stature from little finger lengths. However,  regression equations and multiplication factors are specific to Haryana and nearby  regions only. Other parts of India can have some differences in value in comparison  to our study. The study was carried out on a cross-sectional sample of 145 adult  students from the Haryana region, of which 80 were males and 65 were females.  A significant correlation was observed between little finger length and stature, i.e.,  0.22 in males and 0.20 in females. The current study’s findings show that little  finger lengths are capable of estimating an individual’s stature.
Keywords: Total body height; little finger length; and mean hand anthropometry; Stature; Digit Length